Characterization of electrical properties of β-Ga2O3 epilayer and bulk GaAs using terahertz time-domain ellipsometry. (1st June 2023) - Iwamoto, Toshiyuki; Agulto, Verdad C.; Liu, Shuang; Wang, Youwei; Mag-usara, Valynn Katrine; Fujii, Takashi; Goto, Ken; Kumagai, Yoshinao; Nakajima, Makoto
Abstract: The electrical properties of beta-gallium oxide ( β -Ga2 O3 ) and gallium arsenide semiconductors were characterized using the emerging terahertz time-domain ellipsometry (THz-TDE) technique. The dielectric and conductivity properties were obtained from the complex ratio of the measured p- and s-polarized THz pulses reflected from the samples. The carrier concentration and mobility were then deduced using the Drude model, and the results showed good accuracy. This work demonstrates THz-TDE as a promising tool for characterizing semiconductors, especially those with high carrier concentrations and significant absorption in the THz region.